THE USE OF A PROGRAM IN THE DELPHI PROGRAMMING LANGUAGE WHEN WORKING WITH INTERVALS WITH OBJECTS IN MICROSOFT WORD DOCUMENTS - Azizbek Mahkamov (Web of Journals Publishing, 2024)
This article discusses the importance of working with object-partitioned spaces in Microsoft Word documents. The problem of mixing rows and creating variants is considered. The advantages and disadvantages of converting the object-participating lines to the variant form using a program compiled in the Delphi programming environment are considered.
Keywords: Microsoft Word, Mixing Rows Delphi, Ranges, Rows, Objects Joined. Multimedia educational resources, General secondary schools.